Learning Styles And Factors Affecting Learning: Perception Of 2013/2014 Final Year Post-Diploma Sandwich Students Of The Department Of Basic Education, University Of Education, Winneba (Uew), Ghana - Donkoh, Kweku Esia; Eshun, Emma Sarah; Acquaye, Vivian N. A. (Advances in Social Sciences Research Journal, 2015)
It has been shown through recent studies that it is very necessary to study learning styles because a match between teaching and learning styles helps to motivate students’ processes of learning, hence, the reason for lecturers to identify their own teaching styles and students’ learning styles to obtain better results in the lecture rooms. This study therefore sought to investigate the learning styles of 2013/2014 final year post-diploma sandwich students of the Department of Basic Education, Winneba, Ghana, and the factors that affect their learning. The descriptive survey design was used for the study. The purposive sampling technique was used to sample all four hundred and seventy-two final year students who were given a questionnaire each to be filled. However, four hundred and forty-six students filled their questionnaire and returned them to the researchers. One of the findings was that the most preferred learning style of the students was a combination of auditory and visual learning styles. Another finding was that generally, the students agreed that their learning styles were affected by physical and teaching and learning factors. On the other hand, they generally disagreed that environmental and personal factors influenced their learning styles. It was also found out that physical factors greatly affected the learning styles of 2013/2014 final year post-diploma sandwich students of the Department of Basic Education, Winneba, Ghana. Generally, there was no significant difference in the learning style preference of the male and female students. Among the recommendations is that lecturers of the Department of Basic Education, Winneba, Ghana, should endeavour to identify the learning styles of their students in order to adopt teaching styles that will suit the learning needs of the students.